A Case Report of Naturally Occurring Zinc Deficiency in a Calf, in Elazi?, Turkey - Can, Rauf; Çimtay, Ibrahim; Eröksüz, Yesari (My University, 1999)
It was reportked a case of naturally occurring zinc deficiency in a calf with it's clinical, histopathological, haematological and biochemical findings in province of Eazi?, Turkey. Zinc oxide was administered per orally, in the dose of 100 mg/day for 8 days, and then 40 mg/day for 7 days, and 40 mg/week for 4 weeks. At the end of 8th day of treatment, plasma and hair zinc levels along with plasma alkaline phosphatase level were found to be increased. Though, plasma copper level decreased. Beginning with the treatment, the severity of clinical signs and lesions relieved and completely ceased at the end of treatment.
Elazi? Yöresinde Bir Buza?ida Do?al Çinko Yetersizli?i Olgusu
Keywords: Calf; Parakeratosis; Zinc deficiency